The use of the ECHO model™ for education as an innovative approach to educator professional development - Dahl, Ethan; Sturges, Haley A.; Smith, Olivia K. H.; Hardesty, Canyon; Root-Elledge, Sandra; Zlatkovic, Sarah; Moody, Eric J. (Frontiers in Education, 2023)
After entering the workforce, educators may face novel problems of practice that require additional training. Ongoing professional learning and development (PD) is meant to provide the additional training necessary to ensure educators are prepared to meet those challenges. PD offerings should meet the recommendations of Adult Learning Theory, the Model for Teacher Change, and recommended best practices for adult learning and PD. The ECHO Model for Education is an effective, high-quality model of educator PD that satisfies such recommendations. Practical issues are discussed, and recommendations are made for those interested in implementing this innovative model for PD.